2020
DOI: 10.29359/bjhpa.12.2.06
|View full text |Cite
|
Sign up to set email alerts
|

The examination of some anthropometric and motoric characteristics of students aged eight years according to their maturation level

Abstract: Background: ‪Maturation is an important factor for exercise. The maturation effect on some anthropometric and motoric characteristics of students aged eight years was examined in this study. Material and methods: ‪535 primary education students voluntarily participated in this study. Anthropometric measurements (weight, height, sitting height, stroke length, stroke rate, leg length and body mass index), flexibility, handgrip strength, vertical jump (squat and countermovement jump), tapping (skipping) test pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The test results were used as a criterion for the effectiveness of training. Similar results were obtained in another study (Ari & Deliceoglu, 2020). The results of the finger tapping test made it possible to assess the level of maturation of primary schoolchildren.…”
Section: Introductionsupporting
confidence: 82%
“…The test results were used as a criterion for the effectiveness of training. Similar results were obtained in another study (Ari & Deliceoglu, 2020). The results of the finger tapping test made it possible to assess the level of maturation of primary schoolchildren.…”
Section: Introductionsupporting
confidence: 82%
“…Baumgartner et al [19] believe that moderate physical activity in young athletes is associated with a reduced risk of cardiovascular disease. Other studies [20][21][22][23][24] also emphasize the need to care for the health of children and young athletes in physical activity at various levels. The authors also note the role of parents / coaches and the benefits of gendersensitive physical activity programming.…”
Section: Discussionmentioning
confidence: 99%
“…In the basketball branch, where many changes in body position are required, the transmission of force occurs through the core region in jumping shots or tourniquet shots. Also, it is indicated that muscle mass is important in sport branches requiring strength and power (Ari and Deliceoglu, 2020). Balance and postural control are also provided through the muscles in the core region (Willardson, 2014).…”
Section: Introductionmentioning
confidence: 99%